2014
DOI: 10.3109/00016489.2014.914244
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the clinical approach to the bimodal fitting of hearing aids and cochlear implants: results of an international survey

Abstract: In all, 65 responses were obtained from 12 different countries. All clinicians said they would advise a CI user to wear a contralateral HA if indicated. However, a significant number (45%) had either never fitted HAs before or had less than 1 year of experience. In general, there were no specific criteria for selecting candidates to fit with an HA. A strategy to balance the HA with the CI was not used as a standard practice for any of the adults and was used in only 12% of the children. Only half the responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 18 publications
0
39
0
Order By: Relevance
“…Although adapting HA and/or CI fitting to optimize bimodal benefit is suggested in the literature [Francart and McDermott, 2013], no generally accepted bimodal fitting method exists. In general, the clinical approach described in this study is characteristic of the current course of bimodal practice in CI centres around the world [Scherf and Arnold, 2014].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although adapting HA and/or CI fitting to optimize bimodal benefit is suggested in the literature [Francart and McDermott, 2013], no generally accepted bimodal fitting method exists. In general, the clinical approach described in this study is characteristic of the current course of bimodal practice in CI centres around the world [Scherf and Arnold, 2014].…”
Section: Methodsmentioning
confidence: 99%
“…There is no consensus on which patients are good candidates for the simultaneous use of a CI and a contralateral HA [Scherf and Arnold, 2014], except the presence of usable residual hearing [Offeciers et al, 2005]. The degree of residual hearing in CI patients however has progressively increased over the years, therefore lower bimodal rates may be related to stricter CI candidacy criteria in the past [Ching, 2005].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surveys of “cochlear implant audiologists” reveal that clinicians need guidelines for bimodal candidacy and management (Fielden & Kitterick, 2016; Scherf & Arnold, 2014; Siburt & Holmes, 2015). For instance, it would be helpful to have guidelines regarding the audiologic characteristics of those who actually continue to use a HA postimplantation.…”
Section: Introductionmentioning
confidence: 99%
“…20 Despite the known benefits of bimodal hearing, an international survey showed that an average of only 32% of adult and 26% of pediatric CI patients use a contralateral HA. 21 Sheffield and Gifford 22 showed significant bimodal benefit with low-pass filtered speech with a cutoff as low as 250 Hz, indicating that even patients with limited residual hearing should consider use of a HA. 1 The case for bimodal hearing would not be complete without mentioning the negative effects of auditory deprivation.…”
Section: Benefits Of Bimodal Hearingmentioning
confidence: 99%